توظيف قيم التسامح الديني في المسرح المدرسي: مسرحية مصر لكل المصريين نموذجا: دراسة تحليلية - مسيحة، وجيه جرجس فرنسيس (جامعة المنوفية - كلية الآداب, 2018)
The objective of the research is to: Educate the students of the general secondary stage about the danger of religious fanaticism and the negative effects on the Egyptian society and to identify the factors influencing the dissemination of the values of religious tolerance and its impact on the individual and the Egyptian society. And to identify the intellectual vision and technical treatment of the issue of spreading the values of religious tolerance within the text of the school theater to address the cases and manifestations of intolerance and extremism and extremism and to provide a moderate religious technical discourse objectively addresses the issue of religious tolerance among students of that age. And to highlight the characteristics and characteristics associated with the values of Muslim-Christian religious tolerance. The research was based on the descriptive approach (the content analysis) of the theatrical text "Egypt for All Egyptians" by students of the secondary secondary school for boys. The most important findings of the research: - The text of the school stressed the importance of highlighting the tolerant common denominators in the divine messages and in human civilization in general and in the secondary school community in particular to introduce positive and tolerant behaviors and models in Egyptian society. - The play "Egypt for All Egyptians" stressed the importance of spreading the culture of the values of religious tolerance to the employees of Islamic and Christian religious verses, drawing on the historical evidence that deepens and crystallizes tolerant values. - The author presented positive examples and tolerant religious symbols (Islamic and Christian) within his dramatic fabric such as Sheikh Ahmed Hassan al-Baqouri and Pope Shenouda III as tolerant patriotic models standing against the occupier especially in times of adversity. - Theatrical text "Egypt for all Egyptians" is suitable for the age stage directed at it in terms of containing the feelings and emotions of the teenager and to educate him and warn him of the platforms and channels inflammatory suspicious and yellow books that broadcast and spread the Takfiri and sectarian ideology of our students, through adherence to religious values tolerant Islamic and Christian, The method of family control and civilized dialogue with children to discuss and raise awareness of the scourge of religious intolerance.
Keywords: قيم التسامح -- التسامح الديني -- المسرح المدرسي -- حقوق الإنسان